Language change and morphological processes - Hamans, Camiel (Yearbook of the Poznan Linguistic Meeting, 2017)
Morphological change is not a result of mechanical, predictable processes, but of the behavior of language users. Speakers reinterpret opaque data in order to assign a more transparent structure to them. Subsequently successful reinterpretation may form the basis of new derivations. The moment such a derivative word formation process becomes productive a language change has taken place. In addition, this paper shows how language change obscures the distinction between separate morphological processes such as compounding and derivation and thus between morphological categories. Moreover, the data under discussion show that there is not a preferred natural direction of language change. Most of the examples are taken from English and Dutch, but also a few French, Frisian, German and Afrikaans data are discussed.